Stakeholder perceptions of a nurse led walk-in centre - Parker Rhian M; Desborough Jane L; Forrest Laura E (BMC, 2012)
Abstract Background As many countries face primary care medical workforce shortages and find it difficult to provide timely and affordable care they seek to find new ways of delivering first point of contact health care through developing new service models. In common with other areas of rural and regional Australia, the Australian Capital Territory (ACT) is currently experiencing a general practitioner (GP) workforce shortage which impacts significantly on the ability of patients to access GP led primary care services. The introduction of a nurse led primary care Walk-in Centre in the ACT aimed to fulfill an unmet health care need in the community and meet projected demand for health care services as well as relieve pressure on the hospital system. Stakeholders have the potential to influence health service planning and policy, to advise on the potential of services to meet population health needs and to assess how acceptable health service innovation is to key stakeholder groups. This study aimed to ascertain the views of key stakeholders about the Walk-in Centre. Methods Stakeholders were purposively selected through the identification of individuals and organisations which had organisational or professional contact with the Walk-in Centre. Semi structured interviews around key themes were conducted with seventeen stakeholders. Results Stakeholders were generally supportive of the Walk-in Centre but identified key areas which they considered needed to be addressed. These included the service's systems, full utilisation of the nurse practitioner role and adequate education and training. It was also suggested that a doctor could be available to the Centre as a source of referral for patients who fall outside the nurses' scope of practice. The location of the Centre was seen to impact on patient flows to the Emergency Department. Conclusion Nurse led Walk-in Centres are one response to addressing primary health care medical workforce shortages. Whilst some stakeholders have reservations about the model others are supportive and see the potential the model has to provide accessible primary health care. Any further developments of nurse-led Walk-in Centres need to take into account the views of key stakeholders so as to ensure that the model is acceptable and sustainable.